The effects of harvest date, training system and spacing on physical and chemical characteristics of Physalis fruit - Muniz J.N.* (2014)
The objective of this study was to evaluate the physical-chemical characteristics of fruits of Physalis (Physalis peruviana L.) in the Southern Plateau of Santa Catarina (Brazil) under different training systems, plant spacing and fruit harvest dates. The experimental design was randomized blocks with four training systems (free, vertical trellis, "X" and "V"), two row spacings (3.00 x 0.50 m and 3.00 x 1.00 m). Fruits were harvested thirteen times harvest dates in 2008-2009 and ten in 2009-2010. In 2008-09 harvest, fruits from vertical trellis system (3.00 x 0.50 m) showed the highest size (19.60 mm), soluble solids (13.64°Brix) and SS/TA ratio (8.30). Plants cultivated in the "V" system exhibited lower values for these variables and higher pH values (3.15) and acidity (1.63% citric acid) fruit. In 2009-2010, plants in the "V" system (3.00 x 0.50 m) produced fruits with higher SS/TA ratio (11.77) and fruit pH is 3.85. Plants in the "X" system (3.00 x 1.00 m) had a larger diameter (18.97 mm) and higher vitamin C content (21.16% citric acid) in fruits, compared to all other systems. The highest fruit weight was observed in the vertical trellis system (3.00 x 1.00 m) in both growing seasons (5.27 and 4.71 g, respectively). The free system, among the other systems, presented the lowest weight (3.35 g), diameter (16.70 g) and SS/TA ratio (8.29) in fruits. Thus, it can be claimed that the most appropriate systems for growing Physalis in the Southern Plateau of Santa Catarina (Brazil) are "X" and trellis systems at different spacings.